Thin film polymer photonics : spin cast distributed Bragg reflectors - Bailey, James (2014)
Polymer distributed Bragg reflectors (DBRs) were prepared by spin-casting alternating layers of polystyrene (PS) and poly(vinylpyrrolidone) (PVP) from mutually exclusive (orthogonal) solvents. These all polymer photonic structures were prepared using a purpose built automated spin-coater system. Samples were prepared with targeted optical properties such as the wavelength position, intensity and bandwidth of reflection peaks. The wavelength position of the reflection peaks was controlled by the deposition spin-speed used during sample preparation. Reflectance was controlled by the number of layers deposited onto the sample. The bandwidth was increased by chirping the layers in the photonic structure. Reflection bands were measured in the UV/visible region of the spectrum using two different (transmission and reflection mode) purpose built spectrometer set-ups. Measured reflection bands had narrow bandwidths between 10nm and 20nm. Chirping these photonic structures broadened the peaks to bandwidths of ~ 50nm. A 100 layer PVP/PS DBR had a total reflectance of 93 ± 1%. The wavelength of the reflection peaks from flat DBR samples blue-shifted when measured away from normal incidence. This was reduced when corrugating a DBR by wrinkling the films with mechanical strain. The wavelength of the reflection band from a corrugated DBR remained constant when the sample was rotated. Thus improving the angular dependence of the structures. Fourier transform infra-red spectroscopy was used to measure reflection bands which were between wavelengths of 1600 nm and 2700 nm. These reflection bands had narrow bandwidths between 40 nm and 60 nm. The largest reflectance measured within the infra-red spectra was 80 ± 1% from a 50 layer PVP/PS DBR. A modified optical transfer matrix method was used to model the optical properties of the DBRs. Changes in the refractive index contrast (between 0.020 and 0.028 for 30 layer PVP/PS DBRs) were needed to fit the model to the measured UV/visible spectra. It was concluded that trapped solvent (from sample preparation) was lowering the refractive indices of the layers. The polymer-polymer interface widths of spin-cast polymer multi-layers were measured using neutron reflectivity. Each polymer-polymer interface width was less than 1nm throughout the DBR samples. The polymer multi-layer samples were measured using time of flight secondary ion mass spectrometry (TOF-SIMS). An Ar2000+ sputtering source was used to etch through the multi-layer samples. It was concluded that the thickness of spin-cast films did not change when preparing a multi-layer structure. However, other techniques, such as ellipsometry, are more suitable for measuring the thickness of films. The TOF-SIMS technique was unable to measure polymer-polymer interface widths in multi-layer samples. This was due to the sputtering beam roughening/mixing the polymers at the interfaces. It was concluded that PVP/PS DBRs could be used as inexpensive narrowband reflectors/filters. However, alternative polymer systems may be more useful for other applications which require a greater reflectance. This includes creating resonant cavities to improve the efficiency of optical devices (such as LEDS and solar cells). The results and techniques from these experiments are useful for further development in polymer photonic structures and polymer multi-layer devices.